Benefits of Strength and Skill-based Training During Primary School Physical Education. Issue 5 (May 2015) - Faigenbaum, Avery D.; Bush, Jill A.; McLoone, Ryan P.; Kreckel, Michael C.; Farrell, Anne; Ratamess, Nicholas A.; Kang, Jie
Abstract : Abstract: Faigenbaum, AD, Bush, JA, McLoone, RP, Kreckel, MC, Farrell, A, Ratamess, NA, and Kang, J. Benefits of strength and skill-based training during primary school physical education. J Strength Cond Res 29(5): 1255–1262, 2015—Physical education (PE) programs are evolving from a traditional skill-centered model to a health-centered model that focuses on time engaged in moderate to vigorous physical activity (MVPA). However, improvements in muscular fitness and fundamental movement skills are prerequisites for continuous participation in MVPA. The purpose of this study was to examine the effects of integrative strength and skill-based training on measures of physical fitness in children during primary school PE. Children from two fourth grade PE classes were cluster randomized into either a fundamental integrative training (FIT) group ( n = 20) or a control (CON) group ( n = 21). The 8-week FIT program was performed twice per week during the first ∼15 minutes of each PE class and consisted of a circuit of strength and skill-based exercises. All participants were assessed for health- and skill-related fitness before and after the intervention. The outcome variables were analyzed via 2 × 2 repeated measures analysis of variance with post hoc analysis. A significant ( p ⩽ 0.05) interaction of group by time was observed in FIT participants with improvements in aerobic capacity, push-ups, sit and reach flexibility, and single-leg hop. There were no groups by time effects for the sit-up and long jump tests. No injuries were reported. These findings highlight the potential benefits of integrating both health- and skill-related fitness components into primary school PE as evidenced by improvements in measures of aerobic capacity and muscular fitness in children.